The strengthening of national training systems and required international co-operation: a background paper for the first consultation on the training of industrial manpower (Stuttgart: United Nations Industrial Development Organization, 1982)
The content of this paper have a cross-sectoral bearing which is still valid and topical, and will also meet a hitherto unfilled need in areas like industrial training whose relevance to all other aspects of industrialization is obvious and established.
Prepared by the secretariat of UNIDO in collaboration with the secretariat of ILO and UNESCO.
rpm19/02/2019
Loans
Keywords: Industrial Manpower